2004
DOI: 10.1063/1.1827925
|View full text |Cite
|
Sign up to set email alerts
|

Collection of transverse and longitudinal fields by means of apertureless nanoprobes with different metal coating characteristics

Abstract: The coupling and transmission of transverse and longitudinal fields into apertureless microfabricated near-field optical probes is investigated. Two kinds of probes with different metal coating roughness are considered. Transverse and longitudinal field distributions are obtained by focusing azimuthally and radially polarized beams produced by means of a liquid crystal plate. The focal plane is scanned using microfabricated probes in a collection mode configuration. It is found that the roughness of the metal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Some investigations based on numerical calculations (see, for example, Ref. [4]) and experimental measurements [5,6,7] revealed that the strongest localization of the emitted field is connected to the presence of a longitudinally polarized field. Nonetheless, the main drawback in the exploitation of such a field is the necessity of the probe itself, which is, in general, fragile and difficult to reproduce on a large scale.…”
Section: Introductionmentioning
confidence: 99%
“…Some investigations based on numerical calculations (see, for example, Ref. [4]) and experimental measurements [5,6,7] revealed that the strongest localization of the emitted field is connected to the presence of a longitudinally polarized field. Nonetheless, the main drawback in the exploitation of such a field is the necessity of the probe itself, which is, in general, fragile and difficult to reproduce on a large scale.…”
Section: Introductionmentioning
confidence: 99%
“…This yields an apex angle of 30°, consistent with experimental studies currently being conducted. 12,13 The metal coating is a uniform 50 nm thick layer of aluminum on both the cylindrical and the tapered sections, terminating in a spherical apex of variable diameter (typically 50 nm). Before the subsequent introduction of defects, the probe exhibits a rotational symmetry around the z axis.…”
Section: Background a Modeling Approachmentioning
confidence: 99%
“…2 To better understand the operating characteristics of this class of probes, a considerable amount of work has been performed to optimize their fabrication, as well as to experimentally measure their performance characteristics. [3][4][5][6][7][8] In particular, the properties of the metal coating 9,10 and the polarization state of the light transiting the probe [11][12][13] have been found to play an important role in the optical properties and performance capabilities of the probe. However, as fabricating and testing large numbers of probes with varying configurations is presently impractical, rigorous electromagnetic modeling of such probes has proven to be a useful complement to experimental work in gaining insight into the propagation of light inside and near such probes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many SPP-based superlenses were presented recently [7][8][9] as well as resonance immunosensors [10], nanobiosensors [11] and nanoprobes [12]. One of the superlenses consists of a silver film coating on glass with some corrugations [13].…”
Section: Introductionmentioning
confidence: 99%